Analysis Of Nursing Care in A Case of Osteorthritis and Ginger Warm Compress Treatment In An Elderly Care Home - Salsabila Ukraina, Azzura; Wahyudin (Nursing Case Insight Journal, 2024)
Osteoarthritis (OA) is a joint inflammation commonly referred to as rheumatism, which occurs due to mechanical and biological processes leading to cartilage thinning, joint instability, and calcification. Osteoarthritis is a major cause of disability in the elderly, with an increased risk due to trauma, repetitive joint use, and obesity. Effective management of OA is necessary to prevent complications. Pharmacological treatment is a common management option for OA, with one such intervention being the use of ginger warm compresses. This study aims to analyze the nursing care provided to an elderly patient with osteoarthritis, specifically focusing on the application of ginger warm compress therapy in the Anggrek Room of Griya Lansia, Garut Regency. A case study method was used with a sample of one OA patient. Three priority nursing diagnoses were identified: chronic pain, impaired physical mobility, and knowledge deficit. Nursing interventions included identifying the pain characteristics, applying non-pharmacological pain management through ginger compress therapy, performing active range-of-motion exercises, and providing health education about osteoarthritis. The objective of this study was to gain firsthand experience regarding the effectiveness of ginger warm compress therapy as an intervention for chronic pain in osteoarthritis patients. The study was conducted over three consecutive days with a 15-minute session each day. The results indicated that prior to ginger compress therapy, the patient’s pain level was 5 (moderate pain) on a scale of 0-10. After the intervention, the pain scale decreased to 2 (mild pain), suggesting a significant effect of ginger warm compress therapy in reducing pain in osteoarthritis.